Moral Dimensions of Javanese Forgiveness in Serat Wedhathama and Serat Nitiprana - Suharsono, Suharsono; Mustansyir, Rizal; Murtiningsih, Rr. Siti (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study aims to analyze the moral dimensions of Javanese forgiveness. The data sources are Serat Wedhatama and Serat Nitiprana. The study using hermeneutic, Javanese Ethics, and decency value theory. The results show that the nature of Javanese forgiveness is the embodiment of the virtuous personal character. Forgiveness for virtuous persons is lived and understood as a way of testing and proving the quality of personal morals oriented to inner peace. Forgiveness, which is decided independently and not by social norms, will manifest virtuous personal character.